Soluble TL1A is sufficient for activation of death receptor 3. (24th November 2015) - Bittner, Sebastian; Knoll, Gertrud; Füllsack, Simone; Kurz, Maria; Wajant, Harald; Ehrenschwender, Martin
Abstract : Death receptor 3 (DR3) is a typical member of the tumor necrosis factor receptor family, and was initially identified as a T‐cell co‐stimulatory molecule. However, further studies revealed a more complex and partly dichotomous role for DR3 and its ligand TL1A under (patho)physiological conditions. TL1A and DR3 are not only a driving force in the development of autoimmune and inflammatory diseases, but also play an important role in counteracting these processes through an increase in the number of regulatory T cells. Ligands of the tumor necrosis factor family typically occur in two forms, membrane‐bound and soluble, that can differ strikingly with respect to their efficacy in activating their corresponding receptor(s). Ligand‐based approaches to activate the TL1A–DR3 pathway therefore require understanding of the molecular prerequisites of TL1A‐based DR3 activation. To date, this has not been addressed. Here, we show that recombinant soluble trimeric TL1A is fully sufficient to strongly activate DR3‐associated pro‐ and anti‐apoptotic signaling pathways. In contrast to the TRAIL death receptors, which are much better activated by soluble TRAIL upon secondary ligand oligomerization, but similarly to the death receptor tumor necrosis factor receptor 1, DR3 is efficiently activated by soluble TL1A trimers. Additionally, we have measured the affinity of TL1A–DR3 interaction in a cell‐based system, and demonstrated TL1A‐induced DR3 internalization. Identification of DR3 as a tumor necrosis factor receptor that responds to soluble ligand trimers without further oligomerization provides a basis for therapeutic exploitation of the TL1A–DR3 pathway. Abstract : The molecular prerequisites of ligand‐based Death Receptor 3 (DR3) activation are poorly understood. Here, we demonstrate that the soluble, trimeric form of the DR3 ligand TL1A is fully sufficient to trigger DR3 activation and subsequent internalization. Further oligomerization of TL1A does not enhance specific activity. These findings provide an essential basis for therapeutic exploitation of the TL1A‐DR3 pathway.